PEMBENTUKAN HUFFAZ MELALUI PENERAPAN KONSEP SUFISME DALAM PENDIDIKAN TAHFIZ: THE FORMATION OF HUFFAZ THROUGH THE APPLICATION OF SUFISM CONCEPTS IN TAHFIZ EDUCATION - Saiful Rafizan Jamil; Mardzelah Makhsin; Ahmad Shafie Mohamad, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Pendidikan tahfiz atau penghafalan al-Quran telah menjadi salah satu pendidikan yang arus perdana masa kini. Matlamat utamanya agar melahirkan huffaz yang dapat menghafal 30 juz dengan sempurna. Namun, pendidikan tahfiz tidak hanya menghafal sahaja bahkan memahami ajaran-ajaran Islam yang terkandung dalam al-Quran. Oleh karena itu, penerapan konsep sufisme dalam pendidikan tahfiz dapat membantu membentuk huffaz yang tidak hanya menghafal, tetapi juga memahami dan menyelami ajaran Islam secara lebih dalam. Konsep sufisme juga dikenali sebagai tasawuf dalam pendidikan tahfiz dapat membantu memperkuat hubungan spiritual dengan Allah dan memperkuat keimanan serta ketakwaan seseorang. Para huffaz yang terbentuk melalui pendidikan tahfiz dengan pendekatan sufisme diharapkan dapat memainkan peranan penting dalam mempertahankan keaslian al-Quran, serta membantu meningkatkan pemahaman dan pengalaman spiritual kendiri. Artikel ini bertujuan menganalisis konsep sufisme untuk diterapkan dalam pendidikan tahfiz ke arah pembentukan huffaz cemerlang dan manfaatnya bagi individu, masyarakat, dan umat Islam secara keseluruhan. Tahfiz education or Quran memorization has become one of the mainstream education nowadays. The main goal is to produce huffaz who can memorize 30 juz perfectly. However, tahfiz education is not only memorizing but also understanding the teachings of Islam contained in the Quran. Therefore, the application of the concept of Sufism in tahfiz education can help form huffaz who not only memorize, but also understand and delve deeper into Islamic teachings. The concept of Sufism is also known as Sufism in tahfiz education can help strengthen the spiritual relationship with God and strengthen a person's faith and piety. The huffaz who are formed through tahfiz education with a Sufism approach are expected to play an important role in defending the authenticity of the Qur'an, as well as helping to improve their own spiritual understanding and experience. This article aims to analyze the concept of Sufism to be applied in tahfiz education towards the formation of excellent huffaz and its benefits for individuals, society, and Muslims as a whole.